Expression of Chemoresistance-Related Genes and Heat Shock Protein 72 in Hyperthermic Isolated Limb Perfusion of Malignant Melanoma: An Experimental Study. (7th June 2010) - Knorr, C.; Pelz, J. O.; Göhl, J.; Hohenberger, W.; Meyer, T.
Abstract : Hyperthermic isolated limb perfusion (HILP) is considered an established treatment for multiple locoregional intransit metastases in malignant melanoma of the extremities. Various mechanisms such as the expression of chemoresistance genes and heat shock proteins by the tumor may be responsible for varying response rates and locoregional recurrences of the treatment. The aim of the experimental animal study was to investigate the direct impact of HILP on such mechanisms of resistance. Tissue temperature, administration of the cytostatic drug, and duration of perfusion were varied. Expression of the chemoresistance genes mdr1, mrp1, mrp2, and lrp and of heat shock protein 72 (HSP72) in the tumor tissue was analysed using RT-PCR and western blot analysis. The untreated SK-MEL-3 tumor expressed mdr1, mrp1, and lrp, but not mrp2. Neither variation of temperature, administration of the cytostatic drug, nor duration of perfusion changed the expression of this "resistance pattern". In contrast to the cytostatic drug, hyperthermia causes a persistent induction of HSP72. Both observations could offer a potential explanation for failure of HILP in malignant melanoma.